Ovarian Carcinoma During Pregnancy:Report of Two Cases - Ertan Akpınar; Cantuğ Çalışkan; Alptekin Alagöz; Tayfun Güngör (Medical Network, 2006)
Ovarian tumors during pregnancy are rare events. Although the majority of ovarian tumors complicating pregnancy are benign, they are still important because of the difficulty in differentiating between benign and malign tumors. In most cases, tumors are detected accidentally during routine examination, ultrasound or a caesarean section at term. An ovarian malignancy occuring in association with pregnancy is rare accounting for only 2-5% of ovarian tumors discov ered during pregnancy. Histologic subtypes and prognosis do not differ f rom tumors not associated with pregnancy, it seems howev er, that there are more lesions of borderline malignancy and of low grade. Two cases of pregnancy associated malignant ov arian tumors, one mucinous cystadenocarcinoma and one endometrioid carcinoma are reported. Patient with mucinous cystadenocarcinoma had a history of persistent ovarian tumors during her two pregnancy.